KARAKTERISTIK SOAL UJIAN AKHIR SEMESTER GASAL MATA PELAJARAN FISIKA SMA KELAS X DI KABUPATEN LOMBOK TENGAH NUSA TENGGARA BARAT - Abdul Aziz (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
This study aims to investigate the characteristics of the test items of the end-of-odd-semester final exam of physics of class X high schools made by the subject matter at each high schools in Central Lombok, NTB. This study used the descriptive approach through two stages. First, the qualitative analysis was the study by experts based on the material aspects, constructs, and language to get the information about the ruler of good writing. Second, the quantitative analysis of the data in the form of GPCM politomus scoring models using PARSCALE 4.1 program to obtain the information about the level of difficulty, discrimination power and test informationfunction. The results of this study are as follows. First,the results of the qualitative analysis showed that the characteristics of the item from the material aspectnot available lattice matter, from the aspect of good construct 13 items, and from the aspect of good languages 23 items. Second, the results of the quantitative analysis showed that the characteristics of items received well in SMA A as much as 71%, SMA B as much as 38%,SMA C as much as 50%, SMA D as much as 50%, SMA E as much as 25%, SMA F as much as 40%. Second, the results of quantitative analysis shows that matter to all schools categorized hard total of 12 items, was as much as 5 points, easily as much as 15 grains, and different power items with high category as many as 13 items, was as much as 5 grains and low much as 14 grains, the information function quite well.Keyword: Characteristics about final exam, item response theory, GPCM.